A HERMENEUTIC ANALYSIS OF FILM THE LAST LETTER FROM YOUR LOVER - Fitriyah, Fitriyah; Cahyani, Zahra Dwi (Universitas Islam Sumatera Utara, 2024)
The relationship between past and present is a compelling theme in film, particularly in The Last Letter from Your Lover, which explores love, time, and memory across two eras—the 1960s and the modern day. This study aims to interpret The Last Letter from Your Lover using a qualitative approach, grounded in Gadamer’s hermeneutic theory, to uncover layered meanings that are not directly expressed within the film. The analysis draws on primary data from key film elements, including dialogue, character development, narration, and other cinematic techniques, to provide a nuanced interpretation. Secondary data from academic literature, journals, and articles on hermeneutics supplement the study, offering theoretical depth to the analysis. Findings reveal how themes of love, time, and memory manifest through Gadamer’s concepts of historically effected consciousness, pre-understanding, fusion of horizons, and application. This research aims to contribute to film studies by enhancing understanding of implied meaning through hermeneutic analysis, enriching perspectives on temporal and emotional connections within film narratives.